2003
DOI: 10.1111/j.1745-4514.2003.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Enzyme Activities and Soluble Protein Content in Leaves and Fruits of Olives During Ripening

Abstract: Changes in the content and composition of soluble proteins and the activities of ionically bound peroxidase and polyphenoloxidase in leaves and fruits of olive trees Olea europaea cv. Zard from three regions during “on” and “off” years were evaluated. It was shown that peroxidase and polyphenoloxidase activities were low at early fruit developmental stages, gradually increased and were the highest at full fruit development (120–135 days after fruit set), and remained relatively high throughout ripening and sof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…According to these results and Ebrahimzadeh et al. (2003), it can be concluded that biennial bearing shows a relationship between fruit, leaf and bud, and this research showed this relationship for proteins.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…According to these results and Ebrahimzadeh et al. (2003), it can be concluded that biennial bearing shows a relationship between fruit, leaf and bud, and this research showed this relationship for proteins.…”
Section: Discussionsupporting
confidence: 62%
“…This study on the content and profile of proteins as well as the specific activities of PO and PPO in leaves and buds of olive trees (O. europaea) 45-180 days after fruit set showed a close relationship between these and fruit development. Ebrahimzadeh et al (2003) concluded that there is a close relationship between PO, PPO, specific protein and the process of fruit development. As leaves as sources, and fruits and buds as sinks are considered, transfer of compounds such as proteins from leaves to fruits and buds is necessary for growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…So far there is very few information regarding this subject in olive (Olea europaea). Several studies have partially purified, characterized and identified the cellular location of PPO and POX in olive fruits (Ben-Shalom et al, 1977;Lopez-Huertas and Del Rio, 2014;Saraiva et al, 2007;Shomer et al, 1979;Tzika et al, 2009) and both POX and PPO activities have been investigated during unrelated processes such as browning (Goupy et al, 1991;Sciancalepore and Longone, 1984;Segovia-Bravo et al, 2007) and ripening (Ebrahimzadeh et al, 2003;Ortega-García et al, 2008;Ortega-García and Peragón, 2009).…”
Section: Role Of Oxidative Enzymesactivity and Isoformsmentioning
confidence: 99%
“…Although the low molecular mass for olive PODa1-4 anionic fractions found in this work is rather unusual, similar values were also reported by Khan and Robinson (1993) for two mango isoperoxidases (22 and 27 kDa) and more recently, a 6 kDa peptide from Raphanus sativus was reported as showing peroxidase activity (Omumi et al, 2001). Ebrahimzadeh et al (2003) reported that POD activity in olive increased gradually during fruit development and concomitantly the same authors verified the appearance and increment of peroxidase protein bands at 18-22 kDa, thus pointing to the occurrence of POD isoenzymes with molecular masses in this range in olive fruit.…”
Section: Molecular Weight and Isoelectric Pointmentioning
confidence: 60%